(untitled) (Sainmatika: Jurnal Ilmiah Matematika dan Ilmu Pengetahuan Alam, 2016)
ABSTRACT The research about Pathogenity of fungus Beauveria bassiana Vuill. for Coffea berry bore Hypothenemus hampei Ferr. (Coleoptera: Scolytidae) in July until December 2009 at Microbiology Laboratory of Biology Department, Faculty of Mathematic and Natural Science, University of Sriwijaya, Inderalaya. This research was aimed to know about Pathogenity of fungus Beauveria bassiana Vuill. to coffea berry bore Hypothenemus hampei Ferr. (Coleoptera : Scolytidae) which given with contact test and oral test with suitable lethal (LC 50 ) concentration in effective of conidia B. bassiana for lethal 50% of Pathogenity of fungus Beauveria bassiana Vuill. to coffea berry bore Hypothenemus hampei Ferr. The data of insect mortality of B. bassiana with contact and oral test of (F Test). If there was different about result, would be done The Smallest Significant (BNT) Test with error level 5% and for getting Lethal Concentration Conidia (LC 50 ). The mortality data was analyzed with probit. The result of this research was the effective concentration to control the Pathogenity of fungus Beauveria bassiana Vuill. to coffea berry bore Hypothenemus hampei Ferr. (Coleopteran : Scolytidae) that oral test, LC 50 /6 has that 3,5 x 10 4 conidia/ml more effective than contact test, with LC 50 /4 has that 1,9 x 10 5 . Key words : Beauveria bassiana, Hypothenemus hampei, contact, oral